Mini review: Prevention of mother–child transmission of HIV: 25 years of continuous progress toward the eradication of pediatric AIDS? - Stéphane Blanche (Taylor & Francis Group, 2020)
Prevention of mother-to-child transmission with antiretrovirals is extraordinarily effective. When medically well followed, a mother living with human immunodeficiency virus can now expect to avoid transmitting the virus to her child. Despite the immense difficulties inherent in the global implementation of this treatment, the virtual disappearance of pediatric AIDS can be considered in the long term.